2012
DOI: 10.1088/0264-9381/29/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

On the role of radiation monitors on board LISA Pathfinder and future space interferometers

Abstract: LISA (Laser Interferometer Space Antenna) and its precursor mission LISA Pathfinder (LISA-PF) will carry particle monitors for noise diagnostics. It was proposed to build and place radiation detectors on board the ASTROD missions as well. We present here a study of the solar energetic particle (SEP) events that the LISA-PF radiation monitors are able to detect above the galactic cosmic-ray (GCR) background predicted at the time of the mission data taking in 2015. In order to optimize the correlation between ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…An estimate of the dose released by galactic cosmic rays and solar energetic particles in the polarimeter of the Metis coronagraph was carried out with the Fluka Monte Carlo code. The Gleeson & Axford (1968) model was used to infer the galactic cosmic-ray minimum and maximum projections during the mission on the basis of the interstellar proton spectrum estimated by Shikaze et al (2007) from the BESS experiment data (see Grimani et al 2012, and references therein). Minimum and maximum solar modulation levels were considered according to the strongest and weakest solar cycles of the last 100 years.…”
Section: Metis Radiation Environmentmentioning
confidence: 99%
“…An estimate of the dose released by galactic cosmic rays and solar energetic particles in the polarimeter of the Metis coronagraph was carried out with the Fluka Monte Carlo code. The Gleeson & Axford (1968) model was used to infer the galactic cosmic-ray minimum and maximum projections during the mission on the basis of the interstellar proton spectrum estimated by Shikaze et al (2007) from the BESS experiment data (see Grimani et al 2012, and references therein). Minimum and maximum solar modulation levels were considered according to the strongest and weakest solar cycles of the last 100 years.…”
Section: Metis Radiation Environmentmentioning
confidence: 99%
“…This conservative choice was made in order not to underestimate the actual particle flux reaching the test masses (see for details Ref. 10). We point out that it would be highly recommended to place particle detectors on board the eLISA/NGO and ASTROD missions as well.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 10 we have studied the solar energetic proton events occurred between 1986 and 2004 with associated peak fluxes larger than the GCR background expected in 2015 when the LISA-PF mission will be launched. We have shown that the average fraction of solar energetic protons between 75 MeV and 100 MeV amounts to 45% of those above 100 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…In coincidence mode, 5000 energy deposits per second was the saturation limit. The occurrence of SEP events with fluences larger than the saturation limit was estimated to be less than one per year for the period the LPF spacecraft remained in orbit around L1 (Nymmik 1999a(Nymmik , 1999bGrimani et al 2012). As a matter of fact, no SEP events characterized by a proton differential flux above a few tens of MeV n −1 overcoming that of galactic origin were observed during the period of the LPF mission operations considered for this analysis.…”
Section: Lpf Mission and Orbitmentioning
confidence: 98%